Treatment of starch films with a glow discharge plasma in air and O2 at low pressure. (April 2021) - Sheikhi, Zhian; Hosseini, Seyede Marzieh; Khani, Mohammad Reza; Farhoodi, Mehdi; Abdolmaleki, Khadije; Shokri, Babak; Shojaee-Aliabadi, Saeedeh; Mirmoghtadaie, Leila
In this study, the effect of different cold plasma treatments was investigated as a novel method for the modification of starch film properties. The films were prepared from wheat starch using a solvent casting method and then treated with air and O2 glow discharge plasma at different durations (4, 8, and 12 min). A significant increase in the hydrophilicity of the films was observed due to the formation of oxygen-containing groups after plasma treatment. Fourier transform infrared analysis illustrated a decrease in C–H groups that caused an increase in C–O and C–O–C groups in air-treated films and carbonyl groups in O2 -treated films. The surface roughness of the treated films increased from 17.6 nm to 22.5 and 20.6 nm after air and O2 treatments, respectively. Plasma treatments decreased oxygen permeability of the films but no significant difference in the water vapor permeability was observed. After plasma treatment, tensile strength of films was improved due to crosslinking and etching at the surface, although elongation at break remains unchanged.